Taxonomische Studien zur Hydrophiliden-Gattung Enochrus Thomson, 1859. 2. Teil : Die afrikanischen Arten der Untergattung Methydrus Rey, 1885. A: Die Enochrus meracus-Gruppe (Coleoptera, Hydrophilidae). - Hebauer, Franz (Contributions to Entomology = Beiträge zur Entomologie, 2001)
Phylogenetic reasons in conflict with typologic reasons within the genus Enochrus are caused by the multiple overlapping of the subgenera of that genus. Therefore Balfour-Browne (1958) proposed to facilitate the taxonomic work by subdividing the genus in species groups undependent from phylogenetic viewpoints. Following this way 3 species new to science: E. ituriensis sp. n., E. melinus sp. n., E. mergus sp. n. are described. A key to the African species of the E. meracus-group is given and the aedeagi of all known species are figured. Keywords Insecta, Coleoptera, Hydrophilidae, Enochrus, systematics, taxonomy, Africa, key, new species. Nomenclatural Acts ituriensis Hebauer, 2001 (Enochrus (Methydrus)), spec. n. melinus Hebauer, 2001 (Enochrus (Methydrus)), spec. n. mergus Hebauer, 2001 (Enochrus (Methydrus)), spec. n.